School SPP Payment Information System Multiuser Based: (Case Study of SMA PGRI 1 Purwodadi) - Datu Marta; Khoirur Rozikin; Teguh Setiadi (Lembaga Pengembangan Kinerja Dosen, 2022)
In the current era of globalization, computer users are increasing greatly. Almost every job in school institutions uses computer tools, as is the case at SMA PGRI 1 Purwodadi which is located on Jl. R. Soeprapto No. 34 really need to use a computer. Especially in the school library section which has not been able to utilize sophisticated computer technology in recording school tuition payments. The problem that is often encountered is that in the data processing process, errors are still found during recording in carrying out tuition payment transactions because they are still processed manually by recording them in the book one by one so that the resulting school tuition payment calculations are less accurate. With these problems, the author tries to formulate the problem, namely how to create a computerized school tuition payment program and use a multiuser-based program at SMA PGRI 1 Purwodadi in order to process data more quickly with a minimum error rate. In writing this thesis, the author used Visual Basic 6.0 software and the data base used Microsoft Access